Correlating milk cytokines and somatic cell counts to intramammary infections in dairy sheep - Franzoni, Giulia; Zinellu, Susanna; D’Ascenzo, Vittoria; Giaconi, Emanuela; Denti, Giovanni Vito; Manai, Marina Adele Lucia; Fiori, Angelo; Dei Giudici, Silvia; Bazzardi, Riccardo; Casu, Sara; Carta, Antonello; Fadda, Ilaria; et al. (Frontiers in Veterinary Science, 2026)
Mastitis represents an important health problem in dairy sheep and somatic cell count (SCC) is frequently used as indicator of subclinical intra-mammary infection. Cytokines might represent another reliable and sensitive tool for defining the inflammatory status in relation with the SCC, thus, the levels of 12 key immune cytokines were monitored in ovine milk samples with different SCC values. First, samples were divided into five SCC-groups: group 1 (0–300 cell/mL*1000, n = 16), group 2 (300–500 cell/mL*1000, n = 16), group 3 (500–1,000 cell/mL*1000, n = 16), group 4 (1000–2000 cell/mL*1000, n = 15), group 5 (> 2000 cell/mL*1000, n = 16). Samples belonging to group 5 presented the highest values of IL-1α, IL-β, IL-6, MIP-1α, MIP-1β, IFN-γ, IL-17, IL-10. Samples belonging to group 1 presented IL-4 levels higher than to those belonging to groups 2–3-4, and lower IL-1α and MIP-1α values compared to groups 3–4. Next, cluster analysis was performed. Three clusters were defined: cluster 1 (samples with low SCC values negative to bacterial culture), cluster 2 (samples positive to culture isolation with intermediate SCC values), cluster 3 (samples positive to culture isolation and with high SCC levels). Samples in cluster 1 were characterised by low levels of IFN-γ, IL-1α, IL-1β, IL-6, MIP-1α, whereas samples in cluster 3 presented the highest values of these five cytokines. Samples in cluster 2 presented higher levels of IL-1α and MIP-1α compared to cluster 1, as well as lower levels of IL-4. MIP-1α and IL-1α showed the strongest correlation with SCC values. Overall, our data revealed that intra-mammary infection in dairy sheep was correlated with high levels of pro-inflammatory cytokines in milk samples, which reflect the presence of an inflammatory reaction and confirm the utility of SCC determination in the diagnosis of subclinical mastitis.